La investigación-creación en teología. (2021)
Research-creation is a term that has been gaining special relevance in the fields of the social sciences and humanities. It refers to a mode of production and transmission of knowledge that seeks to expand the limits of research in the current academic context. In this article, we present two academic research-creation experiences developed in the Faculty of Theology of Pontifical Catholic University of Chile, highlighting their contribution to the university and the Church and outlining their disciplinary epistemological status in relation to the so-called "empirical theology".